*This preview shows
pages
1–5. Sign up to
view the full content.*

This ** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*This ** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **Math 3410, Fall 2009 Second semester differential equations 1 Some review 1.1 First order equations We will need to know how to do separable equations and linear equations. A separable equation is one like dy dt = ty 2 . We can rewrite this as dy y 2 = tdt. Integrating both sides,- 1 y = 1 2 t 2 + c, so y =- 1 1 2 t 2 + c . A linear equation is one like y + 2 t y = t. One multiplies by an integrating factor p = e R 2 t = e 2 ln t = t 2 to get t 2 y + 2 ty = t 3 , or ( t 2 y ) = t 3 , 1 which leads to t 2 y = 1 4 t 4 + c, and then y = 1 4 t 2 + c t 2 . When the linear equation has constant coefficients and is homogeneous (i.e., the right hand side is 0), things are much easier. To solve y- 4 y = 0 , we guess a solutions of the form y = e rt , so y = re rt . Then re rt- 4 e rt = 0 , or r = 4, and therefore the solution is y = ce 4 t . To identify c , one needs an initial condition, e.g., y (0) = 2. Then 2 = ce 4 = c, so we then have y = 2 e 4 t . For non-homogeneous equations, such as y- 4 y = e 3 t , one way to solve it is to solve the homogeneous equation y- 4 y = 0, and then use y = ce 4 t + y p , where y p is a particular solution. One way to find a particular solution is to make an educated guess. If we guess y p = Ae 3 t , then we have y p- 4 y p = 3 Ae 3 t- 4 Ae 3 t , and this will equal e 3 t if A =- 1. We conclude the solution to the non- homogeneous equation is y = ce 4 t- e 3 t . 2 1.2 Series From calculus we have the Taylor series e x = 1 + x + x 2 2! + x 3 3! + , cos x = 1- x 2 2! + x 4 4!- , and sin x = x- x 3 3! + x 5 5!- . If i = - 1, substituting and doing some algebra shows that e ix = cos x + i sin x. 2 Second order linear 2.1 Applications First consider a spring hung from the ceiling with a weight hanging from it. Let u be the distance the weight is below equilibrium. There is a restoring force upwards of amount ku by Hookes law. There is damping resistance against the motion, which is- Ru . And the net force is related to accelera- tion by Newtons laws, so ku- Ru = F = mu 00 . This leads to mu 00 + Ru- ku = 0 . If there is an external force acting on the spring, then the right hand side is replaced by F ( t ). The second example is that of a circuit with a resistor, inductance coil, and capacitor hooked up in series. Let I be the current, Q the charge, R the resistance, L the inductance, and C the capacitance. We know that I = dQ/dt . The voltage drop across the resistor is IR , across the capacitor 3 Q/C , and across the inductance coil L dI dt . So if E ( t ) is the potential put into the current, E ( t ) = LQ 00 + RQ + 1 C Q. Sometimes this is differentiated to give E ( t ) = LI 00 + RI + 1 C I. 2.2 Linear, constant coefficients, homogeneous Lets look at an example: y 00- 5 y + 4 y = 0 ....

View Full
Document